ANALISIS STUDI KELAYAKAN INVESTASI PROYEK PEMBANGUNAN MENARA BERSAMA DI KABUPATEN TANGGERANG - , Muhammad Handi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of wireless phones in Indonesia is very fast and aggressive. It can be seen from subscriber growth over the next 5 years are greatly increased. This increase was accompanied by an increase in the number of telecommunication operators, recorded in late 2012, there were 10 wireless telecommunications carriers operating in Indonesia. An increasing number of customers and a significant competitive, requires the operator to expand a large - scale in the infrastucture of a wireless telecommunications infrastructure which can have negative impacts. Seeing this problem, Banten Provincial Government through the Local Government level II Tangerang developing a program which limiting the number of telecommunications towers for efficiency and effectiveness in the use of land as well as managing the tower location with an Investment Project Development, Supply and Management Multi Operator Towers. This paper aims to see the feasibility of the investment Project Development, Supply and Management of multi operator tower in terms of the financial aspect. Financial Analisys using six methods such as NPV, IRR, MIRR, PI, PBP and Sensitivity Analysis. The results of the calculation with NPV method give a positive result, IRR and MIRR give a larger percentage than the cost of capital, the PI is greater than one, and the value of pay-back period less than project economic life. This result suggests strongly that the project is feasible to run.